Sociodemographic and reproductive profile of pregnant teenagers accompanied in the basic health care unit of the municipal district of Canindé - Anna Yáskara Cavalcante Carvalho; Lorena Barbosa Ximenes; Fernanda Cavalcante Fontenele; Regina Cláudia Melo Dodt (Rev Rene)
The study aimed to characterize the socio-demographic and reproductive profi le of pregnant teenagers accompanied by a basic health care unit in the municipal district of Canindé, state of Ceará, in order to verify their social networks of support. The research relies upon a quantitative study made from December 2006 to January 2007 with interviews with 23 adolescents in prenatal care. Of those, 15(65.2%) were aged between 17 to 19 years of age; 12 (52.2%) had incomplete primary school; 21(91.3%) neither had been to school, nor had a job; 14 (60.9%) had had the menarche between 11-12 years of age and coitarche between 15-17 years of age. Still, 20 (87.0%) had made use of some form of contraception; 18 (78.3%) were fi rstborns; 15 (65.2%) admitted that the current pregnancy had been unplanned; 13 (56.5%) had never had sexual education from the family and 16 (69.6%) had never looked for information from health professionals. It was concluded that reproductive issues, such as menarche and early sexual initiation, weak sexual education within family and school environments as well as low demand for health care are directly related do early pregnancy.